Efficiency of Human Expanded Blastocyst Cryopreservation using Vitrification and Collapsing - Yurchuk, Taisiya A.; Petrushko, Marina P.; Pinyayev, Vladimir I. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):167.